An overview of the chemical reaction mechanisms for gasoline surrogate fuels. (September 2017) - Zhen, Xudong; Wang, Yang; Liu, Daming
Highlights: The chemical reaction mechanisms of surrogate fuels for gasoline have been reviewed. The mechanisms for iso-octane, PRF, TRF and multi-component fuels were summarized. This paper put forward some new suggestions in the researches of gasoline mechanisms in the future. Abstract: It is generally accepted that the real petroleum fuels are composed of many various hydrocarbon components. The various gasoline surrogate fuels are typically employed in the computational analysis and engine development. Because of a number of relatively large researches that have been ongoing recently, much progress has been that is worth reporting. This paper systematically describes the developments and progresses of the chemical reaction mechanisms for gasoline surrogate fuels, including the iso-octane, PRF (primary reference fuel), TRF (toluene reference fuel), and multi-component fuels. It introduces the chemical reaction mechanisms of gasoline surrogate fuels based on the detailed chemical mechanisms, the skeleton mechanisms and the reduced mechanisms, respectively. Finally, this paper puts forward some new suggestions on the weakness in the researches of chemical reaction mechanisms for the gasoline surrogate fuels.